Methyl glycosides are identified as glycosyl donors for the synthesis of glycosides, disaccharides and oligosaccharides - Vidadala, Srinivasa Rao; Hotha, Srinivas (Chemical Communications, 2009)
Stable methyl glycosides are identified as glycosyl donors in the presence of AuBr(3) in acetonitrile; a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols are examined successfully for the glycosylation reaction and methyl glycosides of di- and tri-saccharides are converted to corresponding tri- and tetra-saccharides exploiting salient features of our novel activation protocol.